2020
DOI: 10.3390/nu12020494
|View full text |Cite
|
Sign up to set email alerts
|

5-Caffeoylquinic Acid Ameliorates Cognitive Decline and Reduces Aβ Deposition by Modulating Aβ Clearance Pathways in APP/PS2 Transgenic Mice

Abstract: The accumulation of amyloid β (Aβ) in the brain is a major pathological feature of Alzheimer’s disease (AD). In our previous study, we demonstrated that coffee polyphenols (CPP) prevent cognitive dysfunction and Aβ deposition in the brain of an APP/PS2 transgenic mouse AD model. The underlying mechanisms, however, remain to be elucidated. Here, we investigated the effects of the chronic administration of 5-caffeoylquinic acid (5-CQA), the most abundant component of CPP, on cognitive dysfunction in APP/PS2 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…A study published earlier this year has demonstrated chronic administration of 5-Caffeoylquinic Acid (5-CQA) to be effective in reducing Aβ deposition in the APP/PS2 AD mouse model, improving cognitive deficits and neuronal functions: 5-CQA normalised AQP4 perivascular mislocalisation and increased Aβ clearance along the glymphatic system [72], reiterating the importance of AQP4 in this clearance system.…”
Section: Discussionmentioning
confidence: 97%
“…A study published earlier this year has demonstrated chronic administration of 5-Caffeoylquinic Acid (5-CQA) to be effective in reducing Aβ deposition in the APP/PS2 AD mouse model, improving cognitive deficits and neuronal functions: 5-CQA normalised AQP4 perivascular mislocalisation and increased Aβ clearance along the glymphatic system [72], reiterating the importance of AQP4 in this clearance system.…”
Section: Discussionmentioning
confidence: 97%
“…The results indicated that chronic ingestion of CGA ameliorated cognitive deficits and prevented Aβ deposition and neuronal loss in these mice. CGA enhanced the gene expression of hippocampal low-density lipoprotein (LDL) receptor-related protein 1, which has a key role for Aβ clearance and cognitive function maintenance, and restored the perivascular localization of aquaporin 4, which facilitates Aβ clearance [ 43 ]. In a Aβ-induced cell model experiments, Shi et al [ 44 ] found that CGA increased the viability and decreased apoptosis of hippocampal neurons from newborn Sprague–Dawley rats treated with Aβ 25-35 .…”
Section: Alzheimer’s Disease (Ad)mentioning
confidence: 99%
“…Firstly, we investigated in vitro and animal studies. 5-Caffeoylquinic acid may prevent cognitive impairment in mice with Alzheimer’s disease ( Ishida et al, 2020 ). Tangeretin may have therapeutic effects on rheumatoid arthritis in a rat model ( Li et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%